2004
DOI: 10.1063/1.1649455
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency, low-field dielectric spectroscopy of living cell suspensions

Abstract: We have developed a dielectric spectroscopy technique for low-frequencies and low-electric field amplitudes. The excellent sensitivity of this method enables us to apply field amplitudes that are below the linear threshold. The dielectric constants of inorganic and organic liquids are found to be consistent with the previously reported experimental data and theoretical predictions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 10 publications
0
60
0
1
Order By: Relevance
“…Capacitance measurement of cells has been shown to differentiate cells on the basis of their DNA content (65). Although in the original application cells were fixed and suspended in ethanol, it has been suggested that microchip sorters for live cells could be developed based on capacitance measurement principles (66).…”
Section: Microfluidic Flow Cell Sortersmentioning
confidence: 99%
“…Capacitance measurement of cells has been shown to differentiate cells on the basis of their DNA content (65). Although in the original application cells were fixed and suspended in ethanol, it has been suggested that microchip sorters for live cells could be developed based on capacitance measurement principles (66).…”
Section: Microfluidic Flow Cell Sortersmentioning
confidence: 99%
“…One method [6] employs high-T c superconducting quantum interference devices (SQUIDs) to directly probe the tiny ac magnetic fields produced by the displacement currents. Another technique [7] uses conventional electronics, but uses a variable electrode spacing calibration technique to subtract the spurious low-frequency capacitance created by the dipole layers at the electrodes. Groundbreaking work on nonlinear response was spearheaded by Woodward and Kell [8,9], who correlated the generation of harmonics with changes in the conformational states of membrane proteins.…”
Section: Background On Dielectric Spectroscopymentioning
confidence: 99%
“…Dielectric spectroscopy is a powerful method for noninvasively characterizing the properties of biological systems [1][2][3][4][5][6][7][8][9][10][11][12]. It encompasses the frequency dependence of the complex linear dielectric response, which incorporates both the dielectric constant ε(ω) and the conductivity σ (ω) of the medium.…”
Section: Introduction: Background and Motivationmentioning
confidence: 99%
“…We have used successfully this method in the past to remove the polarization error in low conductivity fluids like pure water, toluene, glycol, and for cells suspended in low conductivity buffers [25]. This methodology is based on the observation that Z p is practically independent of the separation distance d between the capacitor's plates.…”
Section: Introductionmentioning
confidence: 99%